U.S.-China digital rivalry and the struggle to shape the world's next order - Seyidbayli, Toghrul (Society Register, 2026)
The emerging digital order, shaped primarily by the strategic rivalry between the United States (U.S.) and China, is transforming global power dynamics and producing significant implications for democracy and multilateral governance. This paper explores how competing digital ecosystems, including social media platforms, cloud services, AI pipelines, and critical infrastructures such as 5G networks and semiconductors, generate asymmetric dependencies, confer strategic leverage, and introduce new vulnerabilities for states and societies. It further analyzes the role of nondemocratic actors in advancing alternative norms, particularly in the domain of cyber governance, that challenge democratic principles and weaken multilateral institutions. Through comparative analysis and the introduction of conceptual tools such as operational depth, the governance AI stack, the computing concentration index, and the allocation intensification gap, the study demonstrates how technological infrastructures are intertwined with political influence, strategic risk, and the erosion of democratic resilience. The findings underscore that safeguarding democracy in the digital era requires not only reinforcing domestic democratic capacities but also establishing multilateral frameworks to mitigate the coercive dimensions of authoritarian digital power.